Metareasoning: Theoretical and Methodological Developments - Linden J. Ball; Beth H. Richardson (Journal of Intelligence)
This Special Issue aims to capture current theoretical and methodological developments in the field of metareasoning, which is concerned with the metacognitive processes that monitor and control our ongoing thinking and reasoning [...]